Measuring English Abilities of Junior High School Students - Afnida, Liza; Adani, Sukri (Jurnal Basicedu, 2024)
Students’ problems in learning English often stem from a lack of exposure to the language, insufficient practice opportunities, and challenges with grammar and vocabulary, which collectively hinder their overall proficiency and confidence. The purpose of this study is to measure students’ ability in mastering English. The method used in this study is a descriptive quantitative approach, conducted at SMP Negeri 3 Kuala Batee. The total number of participants was 27 students, and the data were collected using a test with 50 questions. The results of the study indicated that the students’ ability in mastering English was classified into high, moderate, and low categories. High abilities were evident in mastering main idea identification, understanding text purposes, and recognizing text types. Moderate abilities were observed in conversational skills, identifying supporting details in reading, pronoun reference, passive voice, and word meanings. Low abilities were noted in expressing congratulations and hope, understanding text structure and genres, conversations, simple past tense, comprehension of advertisements, word meanings, and using "to be" and pronouns. These findings suggest that while students have a good grasp of certain aspects of English, significant gaps remain, particularly in grammatical rules and expressive language. The students should learn more about English grammatical rules because this area was categorized into low ability, indicating a need for targeted instructional strategies to address these deficiencies and improve overall language proficiency.